2008
DOI: 10.1248/jhs.54.302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxyhydroquinone-reduced Coffee in Patients with Essential Hypertension

Abstract: Recent animal and human studies suggest that chlorogenic acids, which are the main component of the class of polyphenols in coffee, reduce blood pressure, and that hydroxyhydroquinone (HHQ), produced by roasting green coffee beans, inhibits the antihypertensive effect of chlorogenic acids in brewed coffee. To examine the effects of 4 weeks of daily ingestion of HHQ-reduced coffee in patients with essential hypertension undergoing treatment with antihypertensive drugs. Patients being treated for essential hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Conversely, there are some concerns about potential hepatotoxic effects of green coffee extracts. In an earlier investigation, 2 g of chlorogenic acid/day increased homocysteine concentrations (risk factor for cardiovascular disease) in coffee drinkers [34]. In that study, adverse events appeared, when concentrated green coffee was consumed over a week.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Conversely, there are some concerns about potential hepatotoxic effects of green coffee extracts. In an earlier investigation, 2 g of chlorogenic acid/day increased homocysteine concentrations (risk factor for cardiovascular disease) in coffee drinkers [34]. In that study, adverse events appeared, when concentrated green coffee was consumed over a week.…”
Section: Discussionmentioning
confidence: 85%
“…The characteristics of the included studies are detailed in Table 1. These studies were published between 2005 and 2019 (February) and were conducted in Iran [17,20,29,19], South Korea [32,33], Spain [28], Colombia [31], and Japan [27,30,34,35,36]. The follow-up period ranged from 2 to 12 weeks.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…After percolation, the extract is transferred to a can or other container, and sterilization is performed by exposing the container to high pressure and temperature. Some studies reports that the olfactory (Grosch, 1998;Mayer, Czerny, & Grosch, 2000;Semmelroch & Grosch, 1995) or gustatory (Blumberg, Frank, & Hofmann, 2010;Frank, Blumberg, Krümpel, & Hofmann, 2008;Frank, Blumberg, Kunert, Zehentbauer, & Hofmann, 2007;Frank, Zehentbauer, & Hofmann, 2006) substances that contribute coffee flavor are selectively reduced through the percolation process (Ochiai et al, 2008). In this experiment, we used two types of non-released products (Kao Corporation, Tokyo), samples B and C, among the three samples.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has identified chlorogenic acids (CGAs) that are present in coffee may have an antihypertensive effect and that this may be inhibited by hydroxyhydroquinone (HHQ), which is produced during the roasting of green coffee beans [32,33]. HHQ-reduced coffee has shown some promising results in lowering BP in those with prehypertenison or mild hypertension [34][35][36]; however, one study of patients being treated for essential hypertension revealed no effect on either raising or lowering BP [37]. This interaction of CGA and HHQ may help explain the differential effects of coffee vs. other caffeinated beverages on BP.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%